2015
DOI: 10.1002/micr.22467
|View full text |Cite
|
Sign up to set email alerts
|

The ultrasonographic evaluation of hemodynamic changes in patients with diabetic polyneuropathy after tarsal tunnel decompression

Abstract: According to these results, it can be suggested that the nerve release procedures have a positive effect on the hemodynamic and morphological parameters of the arteries as they pass through the anatomical tunnels as well as its positive effects on the neurological functions of the entrapped nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Tekin et al used US to evaluate the hemodynamic and morphological parameters in posterior tibial and dorsalis pedis arteries. 44 They studied 27 participants with DPN, pre-DNS and 3 months post-unilateral DNS. All measures showed statistically significant improvement post-DNS (described for the posterior tibial artery, as the dorsalis pedis results were comparable).…”
Section: Resultsmentioning
confidence: 99%
“…Tekin et al used US to evaluate the hemodynamic and morphological parameters in posterior tibial and dorsalis pedis arteries. 44 They studied 27 participants with DPN, pre-DNS and 3 months post-unilateral DNS. All measures showed statistically significant improvement post-DNS (described for the posterior tibial artery, as the dorsalis pedis results were comparable).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of Tekin et al concerning ultrasonographic evaluation of hemodynamic changes in patients with DSNP after tarsal tunnel decompression, it can be suggested that nerve release procedures have also a positive effect on the hemodynamic and morphological parameters of the arteries, as they pass through the anatomical tunnels nearby the nerves as well as positive effects on the neurological functions of the entrapped nerves [40].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning applied surgical techniques, it has been seen that minimally invasive surgery for a tarsal tunnel release revealed the similar outcomes compared to open releases [28], at the same time minimizing soft tissue dissection, potential wound complications like infections and scar fibrotization with reducing time recovery and avoiding offloading [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements were maintained or improved further from 3–18 months post-surgery in 36 of 40 limbs and decreased by 1 mm Hg in four. Tekin et al [55] report ND procedures have a positive effect on ultrasonic hemodynamic and morphological parameters (increased pulsatility and decreased resistance) of the dorsalis pedis and posterior tibial arteries.…”
Section: Objective Outcomesmentioning
confidence: 99%